Astratides : insulin-modulating, insecticidal, and antifungal cysteine-rich peptides from Astragalus membranaceus - Huang, Jiayi (2021)
Astragalus membranaceus root, Huang Qi in Chinese, is a popular medicinal herb traditionally used to regulate blood glucose. Herein, the identification and characterization of two families of cysteine-rich peptides (CRPs), designated α- and β-astratides, from A. membranaceus roots are reported. Proteomic analysis showed that α-astratide aM1 and β-astratide bM1 belong to two distinct CRP families. The six-cysteine-containing and proline-rich α-astratide aM1 displayed high sequence identity to Pea Albumin 1 Subunit b (PA1b), while the eight-cysteine-containing β-astratide bM1 showed sequence similarity to plant defensins. An antifungal assay revealed that bM1 possessed potent antifungal activity. In contrast, aM1 showed a cytotoxic effect against insect Sf9 cells. More importantly, aM1 decreased insulin secretion in mouse pancreatic β cells, suggesting it could interfere in glucose homeostasis, which accounts for the adaptogenic property of A. membranaceus. Phylogenetic clustering analysis suggested that the proline-rich aM1 is a putative prolyl oligopeptidase inhibitor and belongs to a novel subfamily of PA1b-like peptides, while bM1 belongs to a new subfamily of plant defensins. Together, the study reveals that astratides are multifunctional CRPs in plants, which expand the existing library of PA1b-like peptides and plant defensins and further our understanding of their roles in host-defense system and leads as peptidyl therapeutics.